Epithelial‐mesenchymal transition‐converted tumor cells can induce T‐cell apoptosis through upregulation of programmed death ligand 1 expression in esophageal squamous cell carcinoma. (31st May 2018) - Thar Min, Aung Kyi; Okayama, Hirokazu; Saito, Motonobu; Ashizawa, Mai; Aoto, Keita; Nakajima, Takahiro; Saito, Katsuharu; Hayase, Suguru; Sakamoto, Wataru; Tada, Takeshi; Hanayama, Hiroyuki; Saze, Zenichirou; et al.
Abstract: Esophageal squamous cell carcinoma (ESCC) is an aggressive tumor, and it is urgently needed to develop novel therapeutic strategies including immunotherapy. In this study, we investigated the upregulation of the programmed death ligand 1 (PD‐L1) due to epithelial‐mesenchymal transition (EMT) in ESCC using an in vitro treatment system with the EMT inducer, glycogen synthase kinase (GSK)‐3 inhibitor, and we also analyzed the correlation of EMT and PD‐L1 expression in the clinical tumor samples of both tissue microarray (TMA) samples (n = 177) and whole tissue samples (n = 21). As a result, the inhibition of GSK‐3β induces EMT phenotype with upregulated vimentin and downregulated E‐cadherin as well as increased Snail and Zinc finger E box‐binding homeobox (ZEB)‐1 gene expression. Simultaneously, we showed that EMT‐converted ESCC indicated the upregulation of PD‐L1 at both protein (total and surface) and mRNA levels. Of importance, we showed that EMT‐converted tumor cells have a capability to induce T‐cell apoptosis to a greater extent in comparison to original epithelial type tumor cells. Furthermore, the immunohistochemical stains of ESCC showed that PD‐L1 expression on tumor cells was positively correlated with EMT status in TMA samples ( P  = .0004) and whole tissue samples ( P  = .0029). In conclusion, our in vitro and in vivo study clearly demonstrated that PD‐L1 expression was upregulated in mesenchymal type tumors of ESCC. These findings provide a strong rationale for the clinical use of anti‐PD‐1/anti‐PD‐L1 monoclonal antibodies for advanced ESCC patients. Abstract : We proved that the epithelial‐mesenchymal transition (EMT)‐converted cancer cells showed the upregulation of the surface expression of programmed death ligand 1 (PD‐L1) and induced the apoptosis of T cells through the PD‐1/PD‐L1 pathway. Furthermore, we showed that PD‐L1 expression on tumor cells was positively correlated with EMT status in surgically resected specimens of esophageal squamous cell carcinoma (ESCC) by the immunohistochemistry. These findings provide a strong rationale for the clinical use of anti‐PD‐1/anti‐PD‐L1 monoclonal antibodies for advanced ESCC patients.